EDITORIAL - de Souza Martins, Lauber (Revista de Engenharia Térmica, 2022)
The editorial of Thermal Engineering of this issue continues the discussion on scientific research needs in vital areas in which thermal engineering has important participation. The main goal is to motivate the readers, within their specialties, to identify possible subjects for their future research. It is estimated that the existing amount of fossil fuels will last for many years. However, there is a need to look for alternative sources of energy in order to preserve the environment. De Angelis et. al., in his article, Energy Research Outlook. What to Look for in 2018 (ACS Energy Lett. 3(2018) 261-263), argues that generation and storage of technical and economically viable renewable forms of energies are the main obstacles to be overcome. In his article, De Angelis also lists some technological areas that need more research effort in the energy field: energy materials, electrochemical energy conversion and energy storage, solar cells, solar fuels, LED and display devices and, the last but not least, theory and computational modeling. Possible answers for those questions can be given from what it is called constructal theory. Constructal theory states that geometry (flow architecture) is generated by seeking the global performance subjected to global restrictions. According to the constructal law, the optimization of the flow architecture begins in a small scale (elementary level), in which, even though small, the system still keeps its identity (e.g., a brook in a river basin, a single polymer electrolyte membrane fuel cell (PEMFC) in a PEMFC stack, a cell in a multicellular organisms). The irreversibility caused by the flow resistance is minimized for a maximum global performance at the level of the complete system. Any physical system is a combination of several flow systems (e.g., electric, chemical, fluid and heat). Therefore, it can be seen that the optimization of the architecture of flow systems is as common in engineering as is in nature, where the most fit organisms (optimum configuration) survive selection (global restrictions). The mission of Thermal Engineering is to document the scientific progress in areas related to thermal engineering (e.g., energy, oil and renewable fuels). We are confident that we will continue to receive articles’ submissions that contribute to the progress of science.